Model Penyaluran Zakat Produktif oleh Baznas Kutai Timur dalam Pemberdayaan Ekonomi Umat - Abdurahim, Alit; Wahab, Abdul; Huda, Sholihul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research is motivated by the need to optimize the management of productive zakat as an instrument for empowering the community's economy, not just for consumption. The East Kutai National Zakat Agency (Baznas) was the object of study because it successfully implemented a structured productive zakat distribution model that has a real impact on the community. The purpose of this study is to analyze the distribution pattern of productive zakat by the East Kutai Baznas and assess its effectiveness in increasing the economic independence of mustahik (recipients). The research method used is a qualitative descriptive case study approach, through in-depth interviews, observation, and documentation of Baznas managers and beneficiaries. The results show that the productive zakat distribution model implemented through the Kutim Sejahtera program integrates capital assistance, entrepreneurship training, business mentoring, and marketing partnerships. Data from 2023–2024 shows an increase in productive zakat funds of 338.8% and a 162.5% increase in the number of beneficiaries, indicating the model's effectiveness in increasing the community's economic capacity. The findings of this study indicate that productive zakat can shift the recipient's paradigm from a consumptive to a productive one. The implications of this research emphasize that institutional strengthening, digitalization of monitoring systems, and cross-sector collaboration are important factors in maintaining the sustainability of productive zakat as a just and effective Islamic economic instrument.